2023
DOI: 10.3390/ijerph20217005
|View full text |Cite
|
Sign up to set email alerts
|

The Sociocultural Influences on Breast Cancer Screening among Rural African Women in South Africa

Nelisha Sarmah,
Maureen Nokuthula Sibiya,
Thandokuhle Emmanuel Khoza

Abstract: The incidence of breast cancer in South Africa is increasing, with rural South African women presenting with advanced stages of the disease. A woman’s breasts are a symbol of her womanhood; they also constitute a social definition of her femininity. Women with breast cancer in rural South Africa are heavily stigmatized and suffer from various sociocultural interpretations of the disease. Breast cancer is frequently interpreted in rural South Africa as a symbol of witchcraft, sin, and punishment, and traditiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“… 40 Moreover, among women in Africa and Middle East, sociocultural factors have been shown to impact early screening and effective treatment of female cancers. 41 , 42 , 43 This is underscored by our study, which identified regions with middle SDI levels, such as Southern Sub-Saharan Africa and North Africa and Middle East demonstrated significant increases in age-standardised DALY rate among WCBA. These increases were driven by both ovarian and breast cancers.…”
Section: Discussionmentioning
confidence: 76%
“… 40 Moreover, among women in Africa and Middle East, sociocultural factors have been shown to impact early screening and effective treatment of female cancers. 41 , 42 , 43 This is underscored by our study, which identified regions with middle SDI levels, such as Southern Sub-Saharan Africa and North Africa and Middle East demonstrated significant increases in age-standardised DALY rate among WCBA. These increases were driven by both ovarian and breast cancers.…”
Section: Discussionmentioning
confidence: 76%